BENTENG AKIDAH: STRATEGI AL-MUQAWWAMAH MENANGKAL AHMADIYAH DI KAMPUNG KONGSI - Triana, Aris; Fahmi, Ami Abdullah; Mulyana, Agus (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2024)
Al-Muqawwamah Islamic Boarding School is one of the Islamic boarding schools in Tasikmalaya Regency which was born in 1982, led by KH. Uoh Syarifudin until 2003, then the leadership was continued by his son KH. Dede Zaenal Abidin from 2003 until now. In this writing, the researcher aims to determine the role of the Al-Muqawwamah Islamic Boarding School in stemming Ahmadiyah ideology in Kongsi Village. Because one of the aims of establishing the Al-Muqawwamah Islamic Boarding School was to counter Ahmadiyah ideology in Kongsi Village, which was once one of the bases for the largest group of Ahmadiyah influence in Singaparna. This article will explain how the Al-Muqawwamah Islamic Boarding School plays a role in stemming Ahmadiyah ideology. In this research the author used a historical method using interview sources and several library sources. . The results of the author's research are that we can find out the development of the Al-Muqawwamah Islamic Boarding School from its inception to becoming one of the Islamic boarding schools that played a role in countering Ahmadiyah ideology in that place. KEYWORDS Ahmadiyah, Al-Muqawwamah Islamic Boarding School, Islamic Religion.